Pengembangan E-Modul P5-PPA Berbasis Thinking Skills untuk Meningkatkan Kreativitas Siswa MI - Aditama, Dhavi Yoga; Mubaidila, Irfa’i Alfian (Jurnal Pendidikan Madrasah, 2026)
This study aims to analyze the validity, practicality, and effectiveness of a thinking skills-based P5-PPA E-module in improving the creativity of fifth-grade students at MI Plus Wildan Assyifa in the 2025/2026 academic year. The study employed a Research and Development (R&D) method using the ADDIE development model, which consists of Analyze, Design, Develop, Implement, and Evaluate stages. Data were collected through expert validation sheets, teacher and student response questionnaires, as well as creativity tests in the form of pre-tests and post-tests. The findings revealed that the developed E-module achieved a validity score of 91% categorized as “Very Valid” based on assessments from material and media experts. The practicality level was also categorized as “Very Practical,” with student responses reaching 88.9% and teacher responses 85%. In addition, the E-module proved effective in enhancing students’ creativity, as indicated by an N-Gain score of 0.620 in the moderate category and an increase in group creativity percentages from 72% to 84%. Therefore, the thinking skills-based P5-PPA E-module is considered feasible, practical, and effective as a learning medium to improve elementary students’ creativity.